Sorghum Tempeh Enteral Formula Reduces Inflammatory (IL-6) and Thrombotic (PAI-1) Markers in Atherogenic Diet-Induced Rats - Bintang, Francisca Natalia; Resti, Nina; Lestari, Endang Sri; Muniroh, Muflihatul; Anjani, Gemala; Syauqy, Ahmad; Djamiatun, Kis; Afifah, Diana Nur (Media Gizi Indonesia, 2026)
Atherosclerosis is predominantly an inflammatory process that is the key pathophysiological cause of ischemic coronary heart disease (CHD). Some studies suggest that sorghum can reduce atherosclerotic parameters through many biological activities, such as antioxidant, anti-inflammation, and anti-thrombotic properties. The primary objective was to evaluate the effect of an enteral sorghum tempeh formula on the levels of Plasminogen Activator Inhibitor-1 (PAI-1) and Interleukin-6 (IL-6) in an atherosclerotic rat model. A total of 24 male rats were utilized, with the experiment structured into an 8-week atherogenic diet induction period, followed by a 4-week intervention phase. The rats were divided into four groups: a healthy control, an atherogenic control, and two treatment groups supplemented with the formula at 0.75g/200 g and 1.50g/200 g body weight (BW), respectively. IL-6 and PAI-1 levels were quantified using Enzyme-Linked Immunosorbent Assay (ELISA). The atherogenic diet successfully induced a significant elevation in both IL-6 and PAI-1 levels compared to the healthy control group (p=0.000), indicating a heightened inflammatory and thrombotic state in the atherosclerotic group. Conversely, the groups receiving the sorghum tempeh-based formula exhibited a significant reduction in both IL-6 and PAI-1 levels compared to the atherogenic control group (p=0.000), suggesting potent anti-inflammatory and antithrombotic properties of the sorghum tempeh.